Design and analysis of DC-DC PWM converter and DC-AC converter - Mazumder, Md Imran Kayesh; Mahbub, Md Munem; Rahman, Muid; Amin, Galib (BARC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.